2015
DOI: 10.1038/nrendo.2014.229
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs as regulators of the endocrine system

Abstract: Long non-coding RNAs (lncRNAs) are a large and diverse group of RNAs that are often lineage-specific and that regulate multiple biological functions. Many are nuclear and are essential parts of ribonucleoprotein complexes that modify chromatin segments and establish active or repressive chromatin states; others are cytosolic and regulate the stability of mRNA or act as microRNA sponges. This Review summarizes the current knowledge of lncRNAs as regulators of the endocrine system, with a focus on the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(157 citation statements)
references
References 123 publications
2
151
0
4
Order By: Relevance
“…Although lncRNAs were previously considered to represent transcriptional noise, with no observable function in cells, it has since been demonstrated that lncRNAs serve a variety of important roles in biological processes, including epigenetic control, the regulation of gene expression, RNA maturation (including splicing and editing) and the maintenance of chromatin structure (3,4,6). Previous studies have revealed that lncRNAs are abnormally expressed in certain tumors, suggesting that they may serve as potential biomarkers predicting the prognosis of patients with cancer (15)(16)(17)(18)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lncRNAs were previously considered to represent transcriptional noise, with no observable function in cells, it has since been demonstrated that lncRNAs serve a variety of important roles in biological processes, including epigenetic control, the regulation of gene expression, RNA maturation (including splicing and editing) and the maintenance of chromatin structure (3,4,6). Previous studies have revealed that lncRNAs are abnormally expressed in certain tumors, suggesting that they may serve as potential biomarkers predicting the prognosis of patients with cancer (15)(16)(17)(18)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Although lncRNAs were once classified as transcriptional noise (5), subsequent studies have demonstrated that lncRNAs participate in various biological processes, including epigenetic control, the regulation of gene expression, RNA maturation (including splicing and editing) and the maintenance of chromatin structure (3,4,6). The abnormal expression of lncRNA has been identified in various types of cancer, including prostate, breast, colorectal, bladder, lung and gastric cancer, as well as hepatocellular carcinoma and melanoma (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are usually lineage specific and regulate multiple biological functions (Knoll et al 2015). In an integrated sequencebased transcriptome and chromatin maps of human islets and β cells, Ferrer and coworkers identified a β cell-specific lncRNA HI-LNC25.…”
Section: Interacting Partners Of Glis3mentioning
confidence: 99%
“…LncRNA have emerged as a novel class of functional RNA and are strongly suspected to regulate genome activities through a broad spectrum of mechanisms (98,121,122) . Pioneering studies by Ferrer and colleagues led to the identification of numerous conserved β-cell-specific lncRNA that are dysregulated in islets of hyperglycaemic T2D donors and often mapping to genomic regions enriched in islet protein-coding genes (123) .…”
Section: Impact Of Nutrients On Non-coding Rna Expression In β-Cellsmentioning
confidence: 99%